Solar-Powered Organic Leaves Waste Shredder Machine with IoT-Based Monitoring Integration - Isa Hafidz; Gilbert Wednestwo Samuel; Christian Jose Anto Kurniawan; Hernadimas Alfattah; Rifki Dwi Putranto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
Organic waste management relying on conventional nonrenewable energy, which produces significant carbon emissions, poses challenges to environmental pollution. A shift to sustainable waste management practices prioritizing renewable energy sources and reducing greenhouse gas emissions is needed. This study aims to design and develop a prototype of an organic waste shredder powered by solar panels, integrating IoT technology to address the environmental impact of traditional shredding methods. The solar-powered shredder is portable and addresses challenges in processing organic waste, especially dry leaves, while promoting renewable energy use in composting. The portable machine operates with a 30-watt, 12-volt DC motor, achieving a maximum speed of 3500 RPM, and features a Blynk-based monitoring system for real-time control and data analysis. Key sensors, including the INA219 and load cell, demonstrate low error rates. The shredder processes various leaf types, with production capacities of 23.96 kg/hour for grape leaves, 20.18 kg/hour for ketapang leaves, 19.93 kg/hour for cherry leaves, and 21.6 kg/hour for mango leaves, achieving 93.09% and 95.17%. The portable power station fully charges in 15 hours and provides up to 18 hours of continuous power. The Blynk application monitors and controls the system within a 9-meter range before disconnection. By integrating solar energy and IoT technology, this device offers a sustainable alternative to traditional shredding methods, reducing carbon emissions and promoting environmentally friendly waste management practices.